Normal breathing releases SARS-CoV-2 into the air. Issue 3 (25th March 2021) - Di Carlo, Piero; Falasca, Katia; Ucciferri, Claudio; Sinjari, Bruna; Aruffo, Eleonora; Antonucci, Ivana; Di Serafino, Alessandra; Pompilio, Arianna; Damiani, Verena; Mandatori, Domitilla; De Fabritiis, Simone; Dufrusine, Beatrice; et al.
Abstract : This study tests the release of SARS-CoV-2 RNA into the air during normal breathing, without any sign of possible risk of contagion such as coughing, sneezing or talking. Five patients underwent oropharyngeal, nasopharyngeal and salivary swabs for real-time reverse transcriptase PCR (RT-PCR) detection of SARS-CoV-2 RNA. Direct SARS-CoV-2 release during normal breathing was also investigated by RT-PCR in air samples collected using a microbiological sampler. Viral RNA was detected in air at 1 cm from the mouth of patients whose oropharyngeal, nasopharyngeal and salivary swabs tested positive for SARS-CoV-2 RNA. In contrast, the viral RNA was not identified in the exhaled air from patients with oropharyngeal, nasopharyngeal and salivary swabs that tested negative. Contagion of SARS-CoV-2 is possible by being very close to the mouth of someone who is infected, asymptomatic and simply breathing.